The nutrition and growth of lambs reared artificially with or without meal : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatu, New Zealand. - Jensen, Amber Celeste Myles (Massey University, 2017)
Artificial rearing is routinely used in large-scale dairy sheep farms. One approach is to offer milk replacer (MR) and meal ad libitum to lambs. The aim was to evaluate the growth of female lambs in the first 12 weeks of rearing with (M) and without (NM) grain-based meal access (n=30/group) during four feeding periods. In period 1 (week 0-3), lambs were offered MR and meal ad libitum, and in period 2 (week 4-5) were transitioned outdoors onto pasture with continued access to MR and meal. Lambs were weaned off MR in period 3 (week 6-10), and meal in period 4 (week 10-12). The NM lambs received identical management, but meal was excluded. A treatment-by-time interaction was found whereby NM lambs had lower average daily gain (ADG) (P<0.05) in periods 1 (376±6 vs. 414±8 g/d) and 3 (146±7 vs. 241±7 g/d), no difference in period 2 (P>0.05), and higher ADG in period 4 (157±18 vs. -55±18 g/d, P<0.05) than M lambs. These results indicate that when lambs fed MR ad libitum are offered unrestricted access to good-quality pasture before weaning, meal may not be required to achieve a similar live weight at 12 weeks of age. Data from the aforementioned experiment were further investigated by week to allow investigations of the relationship between nutrient intake and growth, describe variation in ADG in relation to environmental and feeding transitions, and to estimate pasture intakes, which were not measured. The different feeding transitions, nutrient intakes, and feeds were most likely causing the differences in ADG that occurred between treatment groups and weeks. The greatest variation in ADG of lambs occurred in the M lambs after meal weaning, which was likely due to a poor adaption to a pasture-only diet. Pasture intakes were estimated by calculating lamb requirements for maintenance and growth from actual ADG and live-weight measurements, assuming that pasture intake made up the difference between actual intakes and theoretical intakes. It was found there were significant differences in estimated pasture intakes between M and NM lambs (P<0.0001) and intakes changed over weeks. In weeks seven, eight, and nine, M lambs were estimated to not consume any pasture, due to a high intake of meal, to achieve the observed growth rates. However, NM lambs consumed pasture over these weeks as pasture was their only feed source. These results allow speculation that pasture intake was very low in M lambs before meal was removed. It has been previously reported that high meal intakes when combined with low roughage intake can negatively impact rumen health and development, and transitioning from high meal to high roughage diets requires alterations in the ruminal microbe population and fermentation. The estimated low pasture intake before meal weaning, combined with the high meal intake recorded, may have contributed to the growth check that occurred once meal was removed, as lambs required a period to adapt to the pasture diet, as their rumen underwent the changes associated with transitioning between these diets. Further investigation into differences in pasture intake between lambs reared with and without meal, and more evidence as to what caused the growth check after meal weaning may allow further optimisation of different lamb-rearing systems.
Content removed from thesis for copyright reasons: figure 1.1 (page 14). FAO (2011) Rearing young ruminants on milk replacers and starter feeds, Rome, FAO Animal Production and Health Manual No. 13. http://www.fao.org/docrep/014/i2439e/i2439e00.pdf ; figure 1.2 (page 24). Lane, M., Baldwin, R. L. & Jesse, B. (2000) Sheep rumen metabolic development in response to age and dietary treatments. Journal of Animal Science, 78, 1990-1996. https://www.animalsciencepublications.org/publications/jas/articles/78/7/1990 ; figure 1.3 (page 34). Bimczok, D., Rohl, F. W. & Ganter, M. (2005) Evaluation of lamb performance and costs in motherless rearing of German Grey Heath sheep under field conditions using automatic feeding systems. Small Ruminant Research, 60(3), 255-265. http://www.sciencedirect.com/science/article/pii/S0921448805000027
Keywords: Lambs; Feeding and feeds; Growth; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production::Animal nutrition and management